2017
DOI: 10.1590/1808-1657000142015
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of nematodes biological indicators of soil quality in the agroecosystems

Abstract: Nematodes can be associated with the soil ecological condition, thus being associated with this sustainability condition of agricultural production. Studies of their diversity can be applied with the purpose of using them as bioindicators of environmental changes and the productive impacts. However, these organisms have been neglected in the agroecosystems, only assuming status of pathogen when their population is very high, with considerable losses in productivity. It is estimated that approximately 10% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 57 publications
(54 reference statements)
1
13
0
2
Order By: Relevance
“…Nematode diversity and specific nematode groups (i.e., based on feeding and/or life‐history strategies) or taxa (i.e., family, genus, or species) have been shown to respond differently to soil management such as tillage and fertilization (Moura & Franzener, ; Yeates & Bongers, ). More in detail, previous studies found higher nematode diversity and higher percentages of fungal feeders, omnivores and predators (slow‐growing nematodes of c‐p groups 4 and 5) in less disturbed conditions such as systems under reduced tillage or with perennial crops (Liu et al, ; Niles & Freckman, ; Yeates & Bongers, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nematode diversity and specific nematode groups (i.e., based on feeding and/or life‐history strategies) or taxa (i.e., family, genus, or species) have been shown to respond differently to soil management such as tillage and fertilization (Moura & Franzener, ; Yeates & Bongers, ). More in detail, previous studies found higher nematode diversity and higher percentages of fungal feeders, omnivores and predators (slow‐growing nematodes of c‐p groups 4 and 5) in less disturbed conditions such as systems under reduced tillage or with perennial crops (Liu et al, ; Niles & Freckman, ; Yeates & Bongers, ).…”
Section: Introductionmentioning
confidence: 99%
“…Adubos orgânicos aumentam o pH, nitrogênio mineral, ácido indolacético e respiração basal do solo resultando em aumento da defesa da planta frente ao ataque por nematoides devido a produção de compostos fenólicos radiculares (Xiao et al, 2016;Rao et al, 2017). Sugere-se que nematoides são afetados pela liberação de gases tóxicos e substâncias nematicidas dos adubos orgânicos, há estímulo as defesas da planta pela melhoria da nutrição e há ativação dos organismos do solo que predam ou parasitam os nematoides (Ritzinger & Fancelli, 2006;Moura & Franzener, 2017). Além do efeito nematicida de adubos orgânicos, eles aumentam o crescimento das plantas devido ao fornecimento de nutrientes, promoção do crescimento por microrganismos benéficos, aumento da porosidade e retenção de água, etc.…”
Section: Resultsunclassified
“…This study agrees with the report of Ferris and Bongers (2006), who stated that nematodes are clear indicators of organic enrichment thereby, are reliable bioindicators of organic influx in both the aquatic and terrestrial environments. The absence of Rhaditis terrestri; a short generation life nematode in c-p 1 group indicated poor organic enrichment in the study sites (Bongers, 1990;Zheng et al, 2012;Moura and Franzener, 2017;Nzeako et al, 2019). Nematode community sensitivity in the presence of stress factors in the soil could play a major role in determining the health of the soil ecosystem (Moreno et al, 2011).…”
Section: Trophic Characteristics Of Soil Nematodes In the Studymentioning
confidence: 99%
“…Free living nematodes show positive responses in predictable ways to soil ecosystem disturbances (Freckman and Ettema, 1993;Moody andAitken, 1997, Moura andFranzener, 2017). As the most important secondary consumer in the environment, nematodes are amongst the few meiofauna that readily respond to minute alterations in the physicochemical characteristics of the soil.…”
Section: Introductionmentioning
confidence: 99%